2021
DOI: 10.1111/nyas.14673
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variability in polar sea ice, global atmospheric circulations, and baroclinicity

Abstract: We analyze the polar sea ice distribution and the global sea level pressure (SLP) and baroclinicity distributions over the "satellite" period of 1979-2020. In the Arctic, there are statistically significant sea ice extent (SIE) decreases in all calendar months, and the annual mean has lost 2.22 million km 2 over the four decades. The Antarctic SIE, in marked contrast, increased up to 2014, then commenced a remarkable retreat (the annual mean ice extent decreased by 2.03 million km 2 in the 3 years to 2017), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 157 publications
1
30
2
Order By: Relevance
“…We also note that regions experiencing positive fast-ice trends also coincide with regions experiencing trends toward higher sea-ice concentration. While the time periods of the Simmonds and Li (2021) paper differ to that presented here, we can indeed see that the general distribution of positive trend coincides with the Southern Hemisphere trend in concentration from 1979 to 2020 in September-November (Fig. 2b, bottom row of Simmonds and Li, 2021), but this link is somewhat less convincing for other seasons.…”
Section: Fast-ice Distribution Age and Trendscontrasting
confidence: 50%
See 3 more Smart Citations
“…We also note that regions experiencing positive fast-ice trends also coincide with regions experiencing trends toward higher sea-ice concentration. While the time periods of the Simmonds and Li (2021) paper differ to that presented here, we can indeed see that the general distribution of positive trend coincides with the Southern Hemisphere trend in concentration from 1979 to 2020 in September-November (Fig. 2b, bottom row of Simmonds and Li, 2021), but this link is somewhat less convincing for other seasons.…”
Section: Fast-ice Distribution Age and Trendscontrasting
confidence: 50%
“…While the time periods of the Simmonds and Li (2021) paper differ to that presented here, we can indeed see that the general distribution of positive trend coincides with the Southern Hemisphere trend in concentration from 1979 to 2020 in September-November (Fig. 2b, bottom row of Simmonds and Li, 2021), but this link is somewhat less convincing for other seasons. Nearby pack ice concentration is thought to buffer fast ice against wave-induced break-out (Crocker and Wadhams, 1989) and may also indicate that common environmental forcing is favourable for sea-ice formation/preservation.…”
Section: Fast-ice Distribution Age and Trendscontrasting
confidence: 50%
See 2 more Smart Citations
“…Expanding Hadley cell (or poleward shift of the atmosphere circulation) ties to a systematic poleward shift of the mid-latitude eddy activity (Fig. 4e), which relates to a poleward shift of the baroclinicity (Yin 2005;Mbengue and Schneider 2018;Simmonds and Li 2021). Rudeva et al (2019) found that changes in mid-latitude frontal activity (strong temperature gradients) lead those in the edge of the Hadley cell by approximately one day.…”
Section: Discussionmentioning
confidence: 96%